Establishment of Human Pluripotent Stem Cell‐Derived Skin Organoids Enabled Pathophysiological Model of SARS‐CoV‐2 Infection (Adv. Sci. 7/2022). Issue 7 (4th March 2022) - Ma, Jie; liu, Jia; Gao, Dunqin; Li, Xiao; Zhang, Qiyu; Lv, Luye; Wang, Yujie; Li, Jun; Zhu, Yunping; Wu, Zhihong; Hu, Hengrui; Li, Yufeng; et al.
Abstract : Pathophysiological Model of SARS‐CoV‐2 Infection Human‐induced pluripotent stem cell (hiPSC)‐derived skin organoids can be used to investigate the susceptibility of skin cells to SARS‐CoV‐2 infection, providing the possibility to identify various pathological mechanisms and drug screening strategies. In article number 2104192, Shuyang Zhang, Yiwu Zhou, Manli Wang, Ling Leng, and co‐workers, established an experimental skin organoid model from hiPSC with hair follicles and nervous system and proved KRT17+ hair follicles and different types of nervous cells can be infected by SARS‐CoV‐2, providing the evidence for association between COVID‐19 and hair loss.